2012
DOI: 10.1017/s1751731111002011
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with non-fibrous carbohydrates reduced fiber digestibility and did not improve microbial protein synthesis in sheep fed fresh forage of two nutritive values

Abstract: To determine whether non-fibrous carbohydrate (NFC) supplementation improves fiber digestibility and microbial protein synthesis, 18 Corriedale ewes with a fixed intake level (40 g dry matter (DM)/kg BW 0.75 ) were assigned to three (n 5 6) diets: F 5 100% fresh temperate forage, FG 5 70% forage 1 30% barley grain and FGM 5 70% forage 1 15% barley grain 1 15% molasses-based product (MBP, Kalori 3000). Two experimental periods were carried out, with late (P1) and early (P2) vegetative stage forage. For P2, ewes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Nitrogen (N) compounds of temperate pastures are extensively and rapidly degraded in the rumen (Repetto et al 2005;Fulkerson et al 2007), releasing high amounts of NH 3 to the ruminal environment Cajarville & Pérez et al 2006) that can be utilised by the microbiota. However, the quantity of readily fermentable carbohydrates is often insufficient, leading to low N utilisation and poor animal performance (Elizalde et al 1996;García et al 2000;Tebot et al 2012). This inadequacy is even greater during autumn and early winter, as day length and luminosity are lower, and fewer water-soluble carbohydrates (WSC) are produced by the plants in comparison with late winter and spring (Delagarde et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen (N) compounds of temperate pastures are extensively and rapidly degraded in the rumen (Repetto et al 2005;Fulkerson et al 2007), releasing high amounts of NH 3 to the ruminal environment Cajarville & Pérez et al 2006) that can be utilised by the microbiota. However, the quantity of readily fermentable carbohydrates is often insufficient, leading to low N utilisation and poor animal performance (Elizalde et al 1996;García et al 2000;Tebot et al 2012). This inadequacy is even greater during autumn and early winter, as day length and luminosity are lower, and fewer water-soluble carbohydrates (WSC) are produced by the plants in comparison with late winter and spring (Delagarde et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…This is comparable to the results reported in other studies. For example, Tebot et al. (2012) reported the SD of pasture (90% oat [ Avena sativa ] and 10% white clover [ Trifolium repens ]) DM content was 17 g/kg for pasture cut in the early vegetative stage and 31 g/kg for pasture cut in the late vegetative stage of the harvest season.…”
Section: Discussionmentioning
confidence: 99%
“…The results of these studies supported the hypothesis that there are benefits on microbial protein synthesis in synchronizing the availability of rumen-fermentable carbohydrates with N in the rumen, but this is not always associated with significant changes in rumen pH and NH 3 -N concentrations. Meanwhile, Tebot et al [43] evaluated three forage diets with non-fibrous carbohydrate supplementation (100% fresh temperate forage, 70% forage + 30 barley grain, and 70% forage + 15% barley + 15% molasses-based product). The results indicated that supplementation with starch (barley) or sugars (molasses) in sheep grazing did not improve ruminal N-ammonia captured for microbial protein synthesis.…”
Section: Digestion Of Temperate Forages Plus Other Feedstuffsmentioning
confidence: 99%